Teenagers Perception on the Use English Song in Learning Vocabulary - Meliana Fitri; Suhono Suhono; Rizky Hidayatullah; Mai Zuniati (Bulletin of Science Education, 2023)
The purpose of this research was to investigate and describe the perceptions of teenagers about using English songs in learning English vocabulary. This study used a qualitative approach as a research design. This research was conducted in Metro District, East Metro City. The participants of this study were ten teenagers aged 14 to 17 years. Furthermore, the data was collected from interviews as the main source in this study. This study used thematic analysis to analyze the data findings. The results of this study indicate that teenagers have a positive perspective regarding the advantages of using English songs in learning English vocabulary such as English songs can increase teenagers motivation in learning and increase knowledge about English vocabulary. The researcher also found several challenges faced by teenagers when learning English vocabulary using English songs such as several vocabularies that have different spelling and pronunciation. Keywords: English Song, Learning English Vocabulary, Teenagers Perception